Monomyth – a universal narrative structure in building a brand image - Gielarek-Gorczyca, Krystyna (Linguistic creativity in marketing, 2022)
Building a brand image is a very popular aspect in theory and practice of marketing. The progressive technicization of the society and the multitude of information that reaches the consumers make them feel confused. To make it easier for them to find themselves in the world of promises and persuasions, creative advertisers reach for non-intrusive methods of familiarizing the recipient with the brand. These undoubtedly include storytelling, which constitutes an interesting alternative to imperative traditional forms of advertising communication. The growing popularity of narrative marketing (because this is what storytelling comes down to) is the effect of searching for new manners of reaching a recipient who is tired of explicitly touting messages. Narrative marketing draws themes for its stories from various sources, including Jung's theory of archetypes based on which the concept of a monomyth (that is universal journey of a hero recreated in every mythological story and presently also in popular culture and marketing communication) was created. In the article, I analyze the meaning of myths in contemporary culture – I discuss various research orientations which focus on myths.